Análisis de la eficiencia energética de los sistemas de generación de vapor de la ciudad de Loja. - Infante Toledo, Pedro Mauricio (2012)
This thesis defines all the parameters that govern the energy efficiency of a steam generator. Monitoring and then was collected all necessary data in each of the pots analyzed, which allow to determine the combustion efficiency and each of the heat losses that govern the thermal efficiency. Then we determined the annual operating costs of each boiler and how much is released equivalent to 1% in thermal efficiency over another boiler (thermal efficiency of 100%) in annual operating cost, and then make a estimate of how much I would save if they succeed in improving the heat losses with the exhaust gases and by radiation and convection losses as these are the highest.